Enhanced Spin Accumulation in Semiconductor at Room Temperature Using Ni0.65Zn0.35Fe2O4(NZFO) as Spin Injector in NZFO/MgO/p-Si Device - Maji, Nilay; Shit, Subhasis; Nath, T. K. (Frontiers in Materials, 2021)
In this article, the fabrication of Ni0.65Zn0.35Fe2O4/MgO/p-Si heterostructure device has been optimized utilizing pulsed laser deposition (PLD) technique and the detailed investigation of its structural, electrical and magnetic features have been studied experimentally. The electronic and magneto-transport characteristics have been explored in the temperature range of 100-300 K. The current-voltage (I-V) characteristics of the heterojunction have been recorded which displayed an excellent rectifying magnetic tunnel diode-like behaviour throughout that temperature regime. The application of an external magnetic field parallel to the plane of the NZFO film causes the current (I) across the junction to decrease clearly indicating positive junction magnetoresistance (JMR) of the heterostructure. The root of displaying positive magnetoresistance in our heterojunction has been well justified using the well standard spin injection model. The electrical injection of spin-polarized carriers and its accumulation and detection in p-Si channel have been demonstrated using NZFO/MgO tunnel contact utilizing a three-terminal (3-T) Hanle device. The parameters such as spin life time (99 ps), spin diffusion length (276 nm), and spin polarization (0.44) have been estimated from the Hanle curve detected in our heterostructure at room temperature making Ni0.65Zn0.35Fe2O4/MgO/p-Si device a very favourable promising junction structure in the field of spintronics for several device appliances in forthcoming days. Keywords: Magnetic tunnel diode, heterostructure, mixed spinel ferrite, junction magnetoresistance, spin lifetime, spin polarization, spintronics.